Geochemical alteration of wellbore cement by CO2 or CO2 + H2S reaction during long‐term carbon storage. Issue 5 (22nd March 2016) - Um, Wooyong; Rod, Kenton A.; Jung, Hun Bok; Brown, Christopher F.
Abstract: Cement samples were reacted with CO2 ‐saturated synthetic groundwater, with or without added H2 S (1 wt.%), at 50°C and 10 MPa for up to 13 months (CO2 only) or for up to 3.5 months (CO2 + H2 S) under static conditions. After the reaction, X‐ray computed tomography (XCT) images revealed that calcium carbonate (CaCO3 ) precipitation occurred extensively within the fractures in the cement matrix, while micro‐fractures with aperture size <∼50 μm at the cement‐basalt interface were completely sealed by CaCO3 precipitation. Exposure of a fractured cement sample to CO2 ‐saturated groundwater (50°C and 10 MPa) over a period of 13 months demonstrated progressive healing of cement fractures by CaCO3 precipitation. After reaction with CO2 + H2 S‐saturated groundwater, CaCO3 precipitation also occurred within the cement fracture as well as along the cement‐basalt caprock interfaces. X‐ray diffraction analysis showed that major cement carbonation products of the CO2 + H2 S‐saturated groundwater were calcite, aragonite, and vaterite, all consistent with cement carbonation by CO2 ‐saturated groundwater. While pyrite is thermodynamically favored to form, due to the low H2 S concentration it was not identified by XRD in this study. The cement alteration rate into neat Portland cement samples by CO2 ‐saturated groundwater was similar at ∼0.02 mm/d based on XCT images, regardless of the cement‐curing pressure and temperature (P‐T) conditions, or the presence of H2 S in the groundwater. The experimental results imply that wellbore cement with micro‐fractures within the cement matrix or along the cement‐caprock interface (<∼200 μm aperture under current experimental conditions) is likely to be healed by CaCO3 precipitation during exposure to CO2 ‐ or CO2 + H2 S‐saturated groundwater. Published 2016. This article is a U.S. Government work and is in the public domain in the USA